Eine allgemeine Vignette für Pkfz in Deutschland? - Greinus, Anne; Leypoldt, Patrick; Rommerskirchen, Stefan (Deutscher Verkehrs-Verl., 2007)
Das Thema Pkw-Maut hat spätestens seit Einführung der Lkw-Maut in Deutschland zum 1. Januar 2005 neuen Auftrieb erhalten. Es gibt tatsächlich zahlreiche gute Gründe, die Idee einer Bemautung des Personenkraftfahrzeugverkehrs ernsthaft zu prüfen; bislang wurde diese Diskussion allerdings durch ablehnende Statements der für die Umsetzung verantwortlichen Politiker stets schon im Keim erstickt, wenn - von welcher Seite auch immer - ein entsprechender Vorschlag kam. Der Beitrag zeigt auf, dass eine geschickt gestaltete Vignette für Personenkraftfahrzeuge (Pkfz) in Deutschland sinnvoll und umsetzbar ist. difu

In nations across Europe, present-day motor car toll systems are not compatible due to the application of vastly differing parameters. The requirements of transborder traffic are, therefore, no longer being met, which also applies to road traffic control, guidance, finance and infrastructure. Particularly in Germany, road infrastructure costs are covered mainly by tax revenue and the level of transit traffic is significant on account of its Central European location. Increasingly, calls are made for motor car tolls to be levied since the perpetrator principle should be taken into account more and foreigners should participate in financing Germany's road system. Ongoing discussions tend to be unproductive because they are influenced by inappropriate arguments. Against the background of long-term consultancy work in connection with Germany's transport policy, the authors propose a rather pragmatic solution easily put into practice - namely the introduction of vignettes for motor cars, a move that will offer notable improvements over the current situation. difu
Keywords: Verkehr; Verkehrsmittel; Personenkraftwagen; Bus; Motorrad; Gebühr; Verursacherprinzip; Kraftfahrzeugverkehr; Maut; Vignette; Verkehrsabgabe; Straßenbenutzungsgebühr